2021
DOI: 10.1155/2021/6674336
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension and Associated Factors in Lubumbashi City, Democratic Republic of Congo: A Community-Based Cross-Sectional Study

Abstract: Background. Hypertension is the leading cause of cardiovascular disease morbidity and mortality worldwide. Its struggle involves knowing its prevalence. Insufficient data on hypertension in adults in Lubumbashi, Democratic Republic of Congo (DRC), prompted the conduct of this study. The objectives were to determine the prevalence of hypertension and to identify the associated factors in adults in Lubumbashi. Methodology. A cross-sectional study was carried out among 6,708 adults from October 15th to November 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In the Congolese study conducted in Kinshasa by Connor et al [ 4 ], hypertension was reported as the commonest identifiable risk factor of stroke in 81%. In Lubumbashi (DRC), a community study reported a high prevalence of hypertension (33.6%) [ 12 ], suggesting a high risk of stroke in this population.…”
Section: Introductionmentioning
confidence: 99%
“…In the Congolese study conducted in Kinshasa by Connor et al [ 4 ], hypertension was reported as the commonest identifiable risk factor of stroke in 81%. In Lubumbashi (DRC), a community study reported a high prevalence of hypertension (33.6%) [ 12 ], suggesting a high risk of stroke in this population.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, less frequent intake of vegetables and/or fruits (≤ 5 days a week) was observed in most of the participants (81.4%), and this was significantly associated with the development of HTN; likewise, a community-based study in Addis Ababa revealed that 96.2% of participants consumed vegetables and/or fruits < 5 times per day, and consuming vegetables for ≤ 3 days per week had an increased risk of hypertension (30). Besides, a community-based study done in Lubumbashi City, Democratic Republic of the Congo, showed that nonconsumption of vegetables was significantly associated with HTN (31).…”
Section: Discussionmentioning
confidence: 95%
“…The major difference regarding the DRC MMM21 hypertension prevalence (14.0%) and the rates reported in previous local campaigns such as the VITARAA Study (30.8%) and DRC-MMM-18 (33.5%) in Kinshasa, 3 , 6 the DRC-MMM-19 (25.5%) in Kinshasa and Mbuji-Mayi 7 and the study by Musung et al . 4 (33.6%) in Lubumbashi largely lies on the fact that the present campaign was carried out totally in a semi-rural setting. Indeed, most studies carried out in DRC and elsewhere showed lower BP levels among rural inhabitants than city dwellers who are exposed to different diets and various stressors.…”
Section: Discussionmentioning
confidence: 99%